Clinicopathological Characteristics of Breast Cancer at Cibabat Regional General Hospital in 2022–2023 - Rachmawati, Meike; Acang, Nuzirwan; Purbaningsih, Wida; Robian, Rian; Nugraha, Adhi; Melati, Rina; Aryanti, Aryanti; Anugrah, Aninditya Putri; Laila, Nazmy Noor (Global Medical & Health Communication (GMHC), 2024)
Breast cancer is the most common malignancy found in women throughout the world and is the fifth leading cause of cancer death in the world. Cibabat Regional General Hospital is one of the places for breast cancer examination and treatment in West Java. This study aims to determine the clinical and histopathological features at Cibabat Regional General Hospital. The method used in this research is descriptive-analytic with a total sampling technique using secondary data obtained from the medical records of Cibabat Regional General Hospital patients from 2022 to June 2023. The results show that most cases of breast cancer at Cibabat Regional General Hospital occur in those aged 45–54 (32.3%), left breast (52.1%), grade 3 (44.8%), histopathological type invasive carcinoma of no special type (75%), lymph node status unknown (88.5%), negative lymphovascular invasion (43.7%), and fat invasion status unknown (68.7%). The conclusion is that breast cancer cases at Cibabat Regional General Hospital mainly occur in patients of productive age with a high grade and predominantly in the left breast, with the most common type being invasive carcinoma of no particular type.